Books, Buildings, and Learning Outcomes : An Impact Evaluation of World Bank Support to Basic Education in Ghana - Operations Evaluation Department (Washington, DC: World Bank, 2013)
The Millennium Development Goals aim for universal primary education by 2015 and gender equality in enrolments at all levels of education. The Education for All (EFA) initiative lays out a strategy for achieving these goals. The Bank's own strategy stresses the school quality aspects of EFA, emphasizing the need to focus on preserving learning outcomes while access to education is expanded. This report assesses the impact to date of the efforts over the past 15 years toward increasing the quantity and quality of basic education in one African country, Ghana.